2011
DOI: 10.1002/j.2050-0416.2011.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

How Foam Appearance Influences the Italian Consumer's Beer Perception and Preference

Abstract: The current study presents the results of a survey performed to investigate whether different patterns of foam and lacing affect consumer beer preference and the perception of beer characteristics. The impact of three different levels of foam (huge, medium and little) at pouring, and two lacing patterns (very laced to not laced) during consumption, was evaluated on a set of 26 attributes by a panel of Italian beer consumers. Overall, beers which delivered a medium level of foam at pouring were considered by It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Donadini et al [107] assessed different sensory descriptors, such as carbonation, body, and alcohol, among others, using a hedonic scale with consumers from three different countries: Italy, Poland, and Spain. Other authors have assessed beer acceptability based on the visual assessment of foam using images of three different beers: (i) flat, (ii) medium foam and (iii) high foam, using different techniques, such as the path analysis method of eliminating preferred stimuli [108], preference test with ties and "none" option [109] and using a 7-point Likert scale [110]. In general, these studies concluded that consumers prefer beers with moderate or medium level of foam.…”
Section: Consumer Sensory Analysismentioning
confidence: 99%
“…Donadini et al [107] assessed different sensory descriptors, such as carbonation, body, and alcohol, among others, using a hedonic scale with consumers from three different countries: Italy, Poland, and Spain. Other authors have assessed beer acceptability based on the visual assessment of foam using images of three different beers: (i) flat, (ii) medium foam and (iii) high foam, using different techniques, such as the path analysis method of eliminating preferred stimuli [108], preference test with ties and "none" option [109] and using a 7-point Likert scale [110]. In general, these studies concluded that consumers prefer beers with moderate or medium level of foam.…”
Section: Consumer Sensory Analysismentioning
confidence: 99%
“…Using Bamforth's (2000) stimuli, Donadini et al (2011) assessed the influence of different levels of head (i.e., high, medium, and low) and lacing (present vs. absent) on Italian beer consumers' expectations relating to beer attributes and preferences ( Figure 9 contains images similar to those used by Donadini et al, 2011). Participants were shown different sequences of photographs (i.e., full, half-full, empty) and asked to rate each beer on 26 attributes (e.g., bitterness, ability to quench one's thirst) using a 7-point Likert-type scale, ranging from 1 (strongly disagree) to 7 (strongly agree).…”
Section: Foam (Head and Lacing)mentioning
confidence: 99%
“…As such, corrections for multiple comparisons should be customary. As an example of this issue, Donadini et al (2011) found that the amount of foam consistently influenced people's expectations regarding the attributes of beer. However, given that these authors assessed significance at the .05 level, and given that more than 26 ANOVAs were conducted, it is difficult to determine if the statistically significant differences reported are meaningful.…”
Section: Foam (Head and Lacing)mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount and stability of foam and bubbles are essential in carbonated beverages such as beer since they comprise the most important factors that consumers consider when assessing the quality of beer. According to previous studies, consumers have a preference for beers with a medium level of foam height and consider the low foam as non-desirable with the lowest liking, lowest perceived quality scores, and highest penalty scores [17][18][19][20][21]. Therefore, it is important to explore methods such as sonication during its production process to increase foam in beer.…”
Section: Introductionmentioning
confidence: 99%